UPAYA MENINGKATKAN HASIL BELAJAR MATA KULIAH KEPEWARAAN PADA MAHASISWA PRODI PENDIDIKAN BAHASA INDONESIA DENGAN METODE GUIDED INQUIRY TEACHING MELALUI MEDIA PEMBELAJARAN - Putu Dessy Fridayanthi (Widyadari : Jurnal Pendidikan, 2022)
The presenter is the person in charge of leading and managing the course of an event. An emcee requires skills, knowledge, a pleasant voice and an attractive appearance. The purpose of this study was to determine the responses and learning outcomes of students in the civil service subject at the Indonesian Language Education Study Program, Universitas PGRI Mahadewa Indonesia after the Guided inquiry teaching method was implemented by utilizing learning media. This type of research is classroom action research. This action research is designed using several cycles, where each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The subjects of this study were 12 semester students of the Indonesian Language Education Study Program for the academic year 2021/2022. The object of this research was the student's learning outcomes after being given learning using guided inquiry teaching methods and using visual learning media. The data collection method is the observation method, the test method and the questionnaire/questionnaire method. Based on the results of the study, it can be concluded that (1) There is an effect of the application of the guided inquiry teaching method by utilizing learning media in the civil service course. (2) There is a positive response in the application of the guided inquiry teaching learning method by utilizing learning media in improving the learning outcomes of civility subjects in 6th semester students of the Indonesian Language Education Study Program for the academic year 2021/2022.